Вплив нікотину на функції мітохондрій - Гергалова, Г.Л.; Лихмус, О.Ю.; Коваль, Л.М.; Чернишов, В.О.; Комісаренко, С.В.; Скок, М.В. (Видавничий дім "Академперіодика" НАН України, 2008)
By fluorescent flow cytometry and immunoenzyme techniques, it is shown that nicotine influences the calcium influx into mitochondria through nicotinic acetylcholine receptors expressed on the outer mitochondria membrane.